Factors Affecting Profitability in Indonesia's Retailing sub-sector (2019-2023) - Putri, Nurcika; Fitriani, Dina Amelia; Maiyaliza (Management Institute Faculty of Economics Universitas Andalas, 2025)
This investigation seeks to examine the impact of liquidity and solvency on profitability in retailing sub-sector companies. Liquidity is gauged through the Current Ratio (CR) ratio while solvency uses Debt to Equity Ratio (DER). Profitability is gauged using Return on Equity (ROE). The investigation was executed utilizing a case study method using financial statements to serve as a source of secondary data. The data was examined using multiple linear regression methods to assess the connection involving the independent variables (liquidity and solvency) and the dependent variable (profitability). The findings of this investigation suggest that liquidity does not possess a significant outcome on profitability, while solvency possesses a positive and significant outcome. This research highlights the significance of good liquidity and solvency management in improving the corporation’s financial achievement. The findings are anticipated to be a reference for companies in formulating more effective financial strategies, as well as contributing to further research in the same field.